A prospectus for sustainability of rainfed maize production systems in South Africa. Issue 1 (9th March 2020) - Haarhoff, Stephanus J.; Kotzé, Theunis N.; Swanepoel, Pieter A.
Abstract: The rainfed maize ( Zea mays L.) production systems of South Africa require an integrated approach to use the limited soil available water more efficiently, and to increase system productivity and sustainability. The soils across the major maize production regions are highly susceptible to wind and water erosion. Rigorous soil tillage, maize monoculture, and fallow periods are common, which depletes the soil from organic matter and nutrients. Despite the pressing need for transforming the highly degraded rainfed maize production systems, adoption of more sustainable management approaches has been limited, likely due to a shortage of local scientific field trials to evaluate current and alternative maize agronomic management practices. Erratic interseasonal rainfall patterns cause high variability in maize grain yields. Major challenges associated with no‐tillage are poor crop establishment, subsoil compaction, and high maize grain yield variability. The use of fallow in the maize–fallow production system leads to excessive runoff and soil erosion losses despite increased maize grain yields. Crop intensification and alternative crops are needed to increase rainfall water use efficiency and lower fallow frequency. The use of cover and forage crops may provide the opportunity to diversify and intensify maize production systems. Cover crop biomass could be beneficial in livestock‐integrated production systems providing livestock feed in either winter or summer. Research is drastically required to improve the understanding of current South African rainfed maize production systems and to facilitate the development of fitting sustainable agronomic management practices.